Q. 255.0( 3 Votes )

Find x in terms o

Answer :

We have,



(x – c) [ax + bx – 2ab] = 2c (x2 – bx – ax + ab)


ax2 + bx2 – 2bx – acx – bcx + 2abc = 2cx2 – 2bcx – 2cax + 2abc


ax2 + bx2 – 2cx2 – 2abx + bcx + cax = 0


x2 (a + b – 2c) + x (- 2ab + bc + ca) = 0


x = 0


Or x (a + b – 2c) + (- 2ab + bc + ca) = 0


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses